The Post-War Port Industry Development Models: the Effects on the Economic Development of the Port's Hinterland. - Angeliki Pardali; Constantine Stathopoulou (European Regional Science Association (ERSA), 2006)
The economic development of the port industry that followed the Second World War was based upon two economic theories trends. Until the late 70's the model based on Keynesianism forms the basic idea for ownership, infrastructure, investment, pricing policy and role of ports. Since the early 80's neoliberalism is adopted as a new model of development oversetting what was taken for granted until now and employing a new basis for the port production. Within this framework container ports are the spearhead. The reformed container port industry focuses on container terminals as links in the logistics' chain with effectiveness in port production and in the integrated logistics' chain being their main aim. For this purpose private investment and private port operators come forth. This paper tries to examine whether and in what ways the modern port affects the economic development of its local (port city) or broader (region) hinterland. How is this accomplished in the age of globalized economy?
Keywords: 330